Neonatal Atrial Flutter Approach: A Case Series - Valente, Fernanda Pessa; Góes, Gustavo Henrique Belarmino; Fabro, Caroline Bernardi; Albuquerque, Afonso Luiz Tavares; Sobral Filho, Dário Celestino (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Objective: This study set out to analyze the therapeutic options of patients with neonatal atrial flutter (AFL), considering the diagnostic methods available and the prognosis of these patients. Methodology: A retrospective study was performed by reviewing the medical records of a series of seven patients with atrial fibrillation (AF) diagnosed during fetal or neonatal period. The follow-up time of these patients ranged from 7 months to 3 years and 8 months (mean: 1 year). The clinical data for the diagnosis included sustained heart rate greater than 180 bpm, which was confirmed in all patients by a 12-lead electrocardiogram. Results: Four (57.1%) of the 7 patients studied were male. Most of the patients revealed cardiac arrhythmia during the intrauterine period when screened by fetal ultrasound in the third trimester of gestation (5 patients, i.e. 71.2%). Only the mother of Patient 2 was administered digoxin before childbirth. The atrial rate of the tachyarrhythmia revealed a mean of 375 bpm, with an increase of up to 500 bpm. Atrioventricular conduction presented a 2:1 ratio in all patients, with variations of 3:1 and 4:1 observed in Patients 1, 3 and 6. The ventricular rate ranged from 188 to 250 bpm. All patients revealed typical and counter-clockwise electrocardiogram characteristics. Synchronized electrical cardioversion was the treatment of choice in 6 patients (85.7%), with a dose of 1 J/kg. Conclusion: Early diagnosis, prior treatment, and synchronized electrical cardioversion indicate an excellent prognosis, and prolonged maintenance treatment may be unnecessary.